2015
DOI: 10.1021/cm504330k
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid ZnO-Based Nanoconjugate for Efficient and Sustainable White Light Generation

Abstract: Developing new ways of generating white light is of paramount importance for the design of the next generation of smart, energy-efficient lighting sources. Here we report tunable white light emission of hybrid organic− inorganic nanostructures based on colloidal ZnO nanocrystals conjugated with organic fluorophores. These materials act as single nanophosphors owing to the distance-dependent energy transfer between the two components. The defect-based sizetunable ZnO nanocrystal blue-green emission coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 62 publications
4
48
0
Order By: Relevance
“…The third class of system shown in Fig. 1 is polymerinorganic composites which are characterized by a chemically more complex and often scarcely characterized interface [5,[26][27][28][29]. These materials systems have a variety of advantages which start with the opportunity of self assembly and materials integration into hierarchically organized structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third class of system shown in Fig. 1 is polymerinorganic composites which are characterized by a chemically more complex and often scarcely characterized interface [5,[26][27][28][29]. These materials systems have a variety of advantages which start with the opportunity of self assembly and materials integration into hierarchically organized structures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hybrid structures comprising biopolymers and functional inorganic phases can replace conventional materials in several high technology or bioapplications that are performed in the ambient or under biocompatible conditions. Many nanocomposites are composed of a luminescent organic dye that is attached to or incorporated in the inorganic nanoparticle [5,[26][27][28][29]. Chemical and thermal stability issues as well as materials deterioration via leaching of the luminescence component, however, are continued challenges in the development of this class of material.…”
Section: Introductionmentioning
confidence: 99%
“…The Fourier-transform infrared (FTIR) spectroscopic characterization of this type of nanoconjugates has suggested that binding of dye molecules to the surfaces of transparent metal oxide NCs is facilitated by the carboxyl groups. 30 While RhB can bind through the carboxyl group to NCs dispersed in hexane or toluene, any solvated molecules in such nonpolar solvents exist in the lactone form, which is distinctly nonemissive in orange-red and does not undergo resonance energy transfer due to the negligible intensity of the S 0 → S 1 absorption transition ( Figure S1b). Figure 1b shows an increase in the PL decay rate of Ga 2 O 3 NC trap emission as a result of binding of RhB, which is one of the common characteristics of FRET (see also Figure S2 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We further suggested that rhodamine B (RhB) dye, as a model system, can bind to NC surfaces via the free carboxyl group, allowing for FRET mechanism. 30 In this paper, we quantitatively describe the FRET mechanism involving defect states in Ga 2 O 3 NCs as energy donors and organic fluorophores as energy acceptors to address the origin of white light generation and its control. On the basis of this analysis, we demonstrate the possibility to tune white light by controlling various synthetically accessible parameters, including NC size and surface coverage of dye molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Radovanovic et al. reported ZnO–ATTO fluorophore nanoconjugates for efficient and sustainable white‐light generation by controlling the Förster resonance energy transfer (FRET) process . Li et al.…”
Section: Introductionmentioning
confidence: 99%